Best Kept Secrets - Ellis, Shelly (New York, NY : Dafina Books/Kensington Publishing Corp., 2015)
Between the fall-out from his father's latest shady business dealings and his wife Charisse's alcoholism, Evan Murdoch has his hands full. But he should be most concerned about the scandalous affair Charisse is having right under his nose with his half-brother. Evan's being pushed to the edge, and no one knows that better than Leila Hawkins. Leila is back in Chesterton, divorced, penniless, and desperate enough to do anything to save her mother's home from foreclosure including turning to Evan, her former best friend. But Evan isn't interested in friendship. Instead he makes Leila a shocking indecent proposal. Meanwhile, Evan's newlywed sister, Paulette, wants to be the perfect wife. But a blackmailing bad boy ex has reappeared in her life and he's threatening to reveal her most painful secret. The scandals just won't quit and for everyone involved, desire, betrayal, and lies are all in a day's work.
Keywords: Interpersonal relations -- Fiction; Man-woman relationships -- Fiction; African Americans -- Fiction; Families -- Fiction; Family secrets -- Fiction